The effectiveness of French contract law in the face of Internet giants - Pillet, Gilles (Law, State and Telecommunications Review, 2019)
Purpose ”“ The article analyzes the French contract law in order to assess its usefulness to provide regulatory means of the big techs. It shows that the recent reforms of the French contract law have not been able to empower the consumers and result in a stronger protection against abuse. Methodology/approach/design ”“ The article evaluates the contractual relations between the big techs and their users, with a special regard to the French law (general contract law, the commercial law, and the consumer law). It demonstrates the limits of the general contract law due to the complexity of the contractual subject, named as Internet service. In addition, the article assesses the means of protection: liberty to contract, codes of conduct, and, judicial lawsuits. Findings ”“ The article concludes that the French contract law will only be able to offer effective protective results by benefitting the Internet users if there is an increase of the collective lawsuits, filed by consumers´ protection groups or by state agencies like the Ministry of the Economy. Two other solutions exist, such as codes of conduct and the recognition of more liberty to the users. However, they both have specific limitations to produce effective results.